Ozone-induced adaptive response of ram erythrocytes to cold stress - Zinchenko, V. D.; Golovina, K. N.; Goriacha, I.P.; Volovelskaya, E. L. (Reports of the National Academy of Sciences of Ukraine, 2016)
Ram’s erythrocytes were treated by ozonized physiological solution with ozone concentration of 0.16 mg/l and stored for 12 weeks under hypothermal conditions at +2–+4 ºC in various media: 0.9% sodium chloride solution, 7% sucrose solution, glucose-citrate Alsever’s solution, 5% mannite solution, and 10% dextran solution. Ozone-treated erythrocytes lose the osmotic resistance to a less extent after the storage as compared with non-treated cells. Ozone-treated erythrocytes in the medium with 5% mannite solution preserves the ability to form the rosettes with human lymphocytes after 12 weeks of the storage. The result is explained by the ozone effect on the deformability of erythrocyte membranes.